Death certificate only proportions should be age adjusted in studies comparing cancer survival across populations and over time. (January 2016) - Brenner, Hermann; Castro, Felipe A.; Eberle, Andrea; Emrich, Katharina; Holleczek, Bernd; Katalinic, Alexander; Jansen, Lina; ,
Abstract: Background: The proportion of cases notified by death certificate only (DCO) is a commonly used data quality indicator in studies comparing cancer survival across regions and over time. We aimed to assess dependence of DCO proportions on the age structure of cancer patients. Methods: Using data from a national cancer survival study in Germany, we determined age specific and overall (crude) DCO proportions for 24 common forms of cancer. We then derived overall (crude) DCO proportions expected in case of shifts of the age distribution of the cancer populations by 5 and 10 years, respectively, assuming age specific DCO proportions to remain constant. Results: Median DCO proportions across the 24 cancers were 2.4, 3.7, 5.5, 8.5 and 23.9% in age groups 15–44, 45–54, 55–64, 65–74, and 75+, respectively. A decrease of ages by 5 and 10 years resulted in decreases of cancer specific crude DCO proportions ranging from 0.4 to 4.8 and from 0.7 to 8.6 percent units, respectively. Conversely, an increase of ages by 5 and 10 years led to increases of cancer specific crude DCO proportions ranging from 0.8 to 4.8 and from 1.8 to 9.6 percent units, respectively. These changes were of similar magnitude (but in opposite direction) as changes in crude 5-year relative survival resulting from the same shifts in age distribution. Conclusions: The age structure of cancer patient populations has a substantial impact on DCO proportions. DCO proportions should therefore be age adjusted in comparative studies on cancer survival across regions and over time. Highlights: Death certificate only (DCO) proportions are commonly used data quality indicators in cancer survival studies. We show that they strongly depend on age structures of cancer patient populations. DCO proportions should therefore be age adjusted in cancer survival studies.